Inventarisasi Jenis Paku Terestrial (Pteridophyta) Di Kawasan Wisata Air Terjun Tujuh Tingkat Desa Selamat Kecamatan Tenggulun Kabupaten Aceh Tamiang, Aceh - Ramadani, Risa; Navia, Zidni Ilman; Persada, Andri Yusman (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2021)
The area of the Seven Waterfalls at the Village Level Selamat Tenggulun District has an area that is still beautiful, very supportive for the growth and development of terrestrial nails. This study aims to determine the types of terrestrial ferns in the Seven Level Waterfall Area. The research was conducted from January to May 2020 in the Seven Waterfall Area at Selamat Village Level, Tenggulun District, Aceh Tamiang Regency using the roaming method. The results showed that in the Seven Level Waterfall Area there were as many as 20 species, from 3 nations, 9 tribes, 17 genera of ferns and lived terrestrial, namely Dicranopteris linearis (Burm. F.) Underw, Deparia petersenii (Kunze) M. Kato , Diplazium esculentum (Retz) Sw, Diplazium sandwichianum (C. Precl) Diels, Pleocnemia irregularis (Burm. F.), Blechnum orientale L, Stenochlaena palustris (Burm. F.), Nephrolepis cordifolia (L.) C. Precl, Nephrolepis exaltata (L.) Schott, Drynaria quercifolia (L.) J. Sm, Microsorum scolopendria (Burm. f.) Copel, Adiantum trapeziforme L, Pityrogramma calomelanos L.Link, Pteris biaurita L, Tectaria acerifolia RC Moran, Tectaria decurrens (C. Presl) Copel, Heterogonium pinnatum (Copel.) Holttum, Christella dentata (Forssk) Brownsey & Jermy, Cyclosorus heterocarpus (Blume) Ching and Selaginella sp .